A study on the factor influencing the housing price in Kuching area / Alphonsus Obbermann Anchang and Mohd Izham Ahmar Saberi - Anchang, Alphonsus Obbermann; Ahmar Saberi, Mohd Izham (2017)
This chapter is covered into a number of parts. It begins with the background of study. In background of study we discuss in general the problem occurred related to housing. Next section is focusing on the problem statement. The problem such as urbanization, limited supply of house that cause the increasing of housing price. The research question and research objectives also includes in this chapter. Other than that, we will discuss about the scope of study and significant of study as well. Definition of terms and chapter summary will be the last subtopic in this chapter.